Efeitos da venlafaxina e da vitamina E na periodontite experimental induzida por ligadura em ratos. Avaliação do estado de ansiedade, depressão e perda óssea alveolar - Carvalho, Rosimary de Souza (2010)
The periodontal disease is described as an inflammatory/imunological disease of multifactorial nature that results from an interaction between pathogenic microorganisms and host defense, whose development can be modified by local factors, systemic diseases or genetic factors. Psychosocial events such as stress, anxiety and depression, are few factors which can contribute for the aggravation of the clinical prognostic of many illnesses, including the chronic periodontitis, once it causes an immunological disequilibrium, being able to increase directly the production of proinflammatory cytokines. Oxidative stress has also been related to PD and depression, because of the damages caused to the cellular structures and for compromising the immunological competence. In order to have a greater insight, the present study evaluated the effects of venlafaxine, an antidepressant, and of vitamin E, a known antioxidant, in rat model of ligature-induced experimental periodontitis (EP). The state of anxiety, depression and alveolar bone loss were assessed. Wistar Rats (180-220g) were divided into ten groups: false-operated (SO); EP (vehicle-water); SO and EP + venlafaxine (10 mg/kg e 50 mg/kg); SO and EP (vehicle-oil); SO and EP + vitamin E (500 mg/kg). EP was induced by the insertion of a nylon wire 3.0, around the second upper left molar which remained there for 11 days. Venlafaxine (10 and 50 mg/kg) and vitamin E (500 mg/kg) were administered daily, orally, during 9 days. The behavioral evaluation was made in the 10th day of EP induction by tests of labyrinth in high cross (anxiety) and of immobility in forced swim (depression). The animals were killed by cervical dislocation on day-11 and their jaws removed, for later evaluations. The morphometric analysis showed that the animals submitted to the EP had significant alveolar bone loss (ABL, p<0.001) when compared to the false-operated ones (SO). Venlafaxine (10 mg/kg) attenuated ABL, but it was not statistically significant; on the other hand, it was observed a greater ABL in the group of animals submitted to EP and treated with venlafaxine (50 mg/kg). The histopathological analysis showed in the group submitted to the EP and treated with vehicle (water), significant mononuclear infiltrate (lymphocytes and macrophages), reabsorption of alveolar process (with only bone fragment left) and cement destruction score of 2 (2-3). The group submitted to the EP and treated with venlafaxine (10 mg/kg) also showed similar alterations of the alveolar bone and cementum, with a score of 2 (1-3), otherwise there was no statistical difference. The group SO showed a small or negligible inflammatory infiltrate, score 0 (0-0). Oxidative stress was also the object of evaluation in this study. Increased lipid peroxidation (TBARS) was evident in the group submitted to EP. Venlafaxine (10 mg/kg) reverted it, showing an antioxidant role. Immuno-histochemmical tests were performed (TNF-α and iNOS) in the gingival and periodontal tissues of the animals revealed an increased immunoreactivity scores in the group of animals submitted to EP, compared to SO group. Venlaflaxine treatment did not reduce these scores. Morphometric analysis of the jaws from EP rats treated with vitamin E (500mg/kg) showed no protection from ABL, when compared to EP controls. The histopathological analysis showed less mononuclear infiltrate in the group submitted to the EP and treated with vitamin E, score 2(0-3) when compared with the group EP, 3 (2-3). The oxidant stress evaluation through the measurement of lipid peroxidation (TBARS) and the activity of the enzyme superoxide dismutase (SOD) showed a significant increase in the concentration of MDA (µM) as well as SOD in animals on EP. Treatment with vitamin E (500 mg/kg) prevented the lipid peroxidation (p<0.05), and also showed a small decrease in SOD activity. The evaluation for TNF-α and iNOS immunoreactivities, EP rats showed an increased immunoreactivity scores for both TNF-α and iNOS, treatment with vitamin E reduced the immunoscores for iNOS only. The behavioral evaluation demonstrated that EP was not associated with anxiety or depression. As regards to body weight changes, rats on EP gained less body weights in the first days of induction of EP. Venlafaxine and vitamin E treatments did not change these results. These data allow us to conclude that venlafaxine as well as vitamin E treatments do not prevent ABL. Venlafaxine (IRSNs) is susceeptible to exarcerbate the ABL in EP when used in high dose. Attention should also be given to the indiscriminate use of antioxidants. The use of vitamin E showed anxiogenic effect.